2003
DOI: 10.1021/jf0261957
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effects of Lactic Acid Bacteria on the Colonic Mucosa of Iron-Overloaded Mice

Abstract: The antioxidative effects of lactic acid bacteria on lipid peroxidation in the colonic mucosa were investigated. Among 49 strains of lactic acid bacteria, Streptococcus thermophilus YIT 2001 showed the highest inhibitory activity against lipid peroxidation in liposomes induced by ferrous iron. Feeding a diet containing 0.4% St. thermophilus YIT 2001 (2 x 10(8) colony-forming units per mouse per day) for 2 weeks caused a significant decrease of lipid peroxide (thiobarbituric acid reactive substance) in the colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
4
33
0
1
Order By: Relevance
“…In previous studies, oral administration of Bifidobacterium bifidum strain Yakult effectively decreased colonic oxidative stress induced by an iron overload diet (17,18). It has also been reported that Streptococcus thermophilus YIT 2001 protected the colonic mucosa against oxidative stress (17).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In previous studies, oral administration of Bifidobacterium bifidum strain Yakult effectively decreased colonic oxidative stress induced by an iron overload diet (17,18). It has also been reported that Streptococcus thermophilus YIT 2001 protected the colonic mucosa against oxidative stress (17).…”
Section: Discussionmentioning
confidence: 90%
“…It has also been reported that Streptococcus thermophilus YIT 2001 protected the colonic mucosa against oxidative stress (17).…”
Section: Discussionmentioning
confidence: 97%
“…43) Ito et al reported that 2 weeks of a diet containing 0.4% Streptococcus thermophilus YIT 2001 (2ϫ10 8 cfu/d) induced a significant reduction in lipid peroxides (thiobarbituric acid reactive substances) in the colonic mucosa of iron-overloaded mice. 44) In our previous study, the administration of B. polyfermenticus has been shown to colonize the human intestine, thereby reducing the numbers of fecal coliforms in healthy adults. 45) Therefore, B. polyfermenticus has been theorized to function as a non-absorbable antioxidant in the colon or at the surface of the colonic mucosa, similarly to other lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…45) Therefore, B. polyfermenticus has been theorized to function as a non-absorbable antioxidant in the colon or at the surface of the colonic mucosa, similarly to other lactic acid bacteria. 44) It might also be hypothesized that, although the majority of B. polyfermenticus taken orally has been determined to reach the intestines in endospore form, 20) some of the bacteria might be expected to lyse during transit through the gastrointestinal tract, and to release their intracellular antioxidative constituents. The absorbed antioxidants from the small intestine then subsequently flow to the circulation, and may function as antioxidants in blood, thereby resulting in increased plasma TRAP levels and decreased lipid peroxidation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that some lactobacilli possess antioxidative activity, and could decrease the risk of accumulation of reactive oxygen species during the ingestion of food (Ito, et al, 2003;Kuda et al, 2010). However, probiotic bacteria must be resistant to the acidity of the stomach, lysozyme, bile, pancreatic enzymes.…”
Section: Groupmentioning
confidence: 99%